Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Dividen terhadap Nilai Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Randika Saputra; Masril Masril; Safrizal Safrizal (Goodwood Akuntansi dan Auditing Reviu, 2023)
Purpose: Firm value is the investor's perception of the company associated with the stock price. This study aims to determine the effect of investment decisions, funding decisions, and dividend policies on firm value. Methodology/approach: The data analysis technique uses multiple linear regression analysis using SPSS. The population in this study are all manufacturing companies in the food and beverage sub-sector which are listed on the Indonesian stock exchange from 2019 to 2022, totaling 43 companies. The sampling technique in this study used purposive sampling. The sample in this study amounted to 11 companies that have been determined. Results/findings: The results showed that simultaneously the investment decision variables, funding decisions and dividend policy have an effect on firm value variables, while partially investment decisions have an effect on firm value, funding decisions have no effect on firm value, and dividend policy has an effect on firm value Limitations: The scopes in this study is to focus on the analysis of company value which is influenced by investment decisions, funding, and dividend policies Contribution: The contribution from the results of the research conducted shows that firm value is influenced by investment decisions and dividend policy in the research model used Novelty: The update in this research illustrates a theoretical study of company value analysis in food and beverage sub-sector manufacturing companies with quantitative analysis.